Indonesian EFL Undergraduates Perceptions of Intercultural Learning in a Cross-Cultural Understanding Course - Ana Elvia Jakfar; Any Elvia Jakfar; Endah Anisa Rahma; Jusnaini Hasni; Ainol Mardhiah (Pencerah, 2026)
English language learners are expected to interact with people from a variety of cultural backgrounds in the globalized world. As a result, intercultural competency is now a crucial part of teaching English as a foreign language (EFL). This study investigates how EFL students view the contribution of Cross-Cultural Understanding (CCU) classes to the development of intercultural competency. 10 undergraduate EFL students who had enrolled in a CCU course at Universitas Teuku Umar participated in semi-structured interviews to gather data using a qualitative method. The results show that CCU courses improve students' understanding of cultural diversity, empathy, openness, communication skills, and cultural awareness. In addition, students claimed that conversations in the classroom and exposure to real cultural activities helped them challenge stereotypes and develop more positive views toward different cultures. According to the study's findings, CCU courses are crucial in helping EFL students develop intercultural competency and get ready for global communication.